2015
DOI: 10.18632/oncotarget.3045
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of C1GALT1 promotes breast cancer cell growth through MUC1-C signaling pathway

Abstract: Aberrant glycosylation is frequently observed in cancers. Core 1 β1,3-galactosyltransferase (C1GALT1) is an exclusive enzyme in humans that catalyzes the biosynthesis of core 1 O-glycan structure, Gal-GalNAc-O-Ser/Thr, whose expression is commonly up-regulated during tumorigenesis. Little is known about the function of C1GALT1 in breast cancer. This study aims to determine the correlation between C1GALT1 expression and breast cancer clinicopathological features and roles of C1GALT1 in breast cancer malignant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
41
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 46 publications
3
41
0
1
Order By: Relevance
“…Our results are consistent with recent reports that show higher C1galt1 gene expression in human breast cancer relative to non-cancerous breast tissue (8,9). In addition, increased C1galt1 expression in tumor tissue has been associated with enhanced Muc1 function and advanced tumor stages (9).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results are consistent with recent reports that show higher C1galt1 gene expression in human breast cancer relative to non-cancerous breast tissue (8,9). In addition, increased C1galt1 expression in tumor tissue has been associated with enhanced Muc1 function and advanced tumor stages (9).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, increased C1galt1 expression in tumor tissue has been associated with enhanced Muc1 function and advanced tumor stages (9). Our study provides evidence that elimination of core 1 O-glycosylation alters the expression pattern of Muc1 in both non-transformed and transformed mammary epithelial cells in vivo and results in decreased Muc1 signaling associated with cell proliferation.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…17,18 Moreover, we recently reported that C1GALT1 alters O-glycans on hepatocyte growth factor receptor, also known as MET, and enhances MET dimerization in hepatocellular carcinoma 19 ; modifies O-glycans on fibroblast growth factor receptor 2 and its downstream signaling involved in colorectal cancer malignant phenotypes 20 ; and enhances breast cancer malignant progression by modulating O-glycans on Mucin (MUC) 1 and promoting MUC1-C/Acatenin signaling pathway. 21 Although C1GALT1 and mucintype O-glycosylation have been shown to play crucial roles in a variety of biologic functions, the roles of C1GALT1 in ovarian cancer remain unclear.…”
mentioning
confidence: 99%